PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR TIGA DIMENSI TERHADAP KREATIVITAS MENGGAMBAR SISWA MATERI SBDP - Gusti Ulfa Sari; Noviati; Rury Rizhardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the implementation of the Project Based Learning model assisted by three-dimensional image media on students’ drawing creativity in SBDP subject at SD Negeri 38 Palembang. This study used a quasi- experimental quantitative method with a Nonequivalent Control Group Pretest-Posttest Design. The sample consisted of an experimental class and a control class. Data collection techniques were conducted through observation and assessment of students’ drawing creativity. Data analysis was carried out using normality test, homogeneity test, and hypothesis testing (independent sample t-test) with the assistance of SPSS application. The results showed that the average score of students’ drawing creativity in the experimental class was 13.35 with a standard deviation of 2.262, while the control class obtained an average score of 11.25 with a standard deviation of 2.436. The hypothesis test result showed a significance value (Sig. 2-tailed) of 0.008 ≤ 0.05, therefore H0 was rejected and H1 was accepted. This indicates that the implementation of the Project Based Learning model assisted by three-dimensional image media had a significant effect on students’ drawing creativity in SBDP subject at SD Negeri 38 Palembang.